Pigmented neurofibroma with hypertrichosis - Juan A. Godínez-Chaparro; Adriana M. Valencia-Herrera; Carlos A. Mena-Cedillos; Sonia Toussaint-Caire; Mario R. Duarte-Abdala; Omar Loza-Escutia; Mirna E. Toledo-Bahena (Permanyer, 2023)
Background: Pigmented (or melanocytic) neurofibroma (PN) constitutes only 1% of cases and is considered a rare variant of neurofibroma containing melanin-producing cells. In addition, the association of PN with hypertrichosis is infrequent. Case report: We describe the case of an 8-year-old male with a neurofibromatosis type 1 (NF1) diagnosis, who presented a light brown hyperpigmented plaque, smooth and well-demarcated, and hypertrichosis on the left thigh. The skin biopsy showed characteristics of neurofibroma; however, in the deep portion of the lesion, melanin deposits positive for S100, Melan-A, and HMB45 were observed, thus establishing the diagnosis of pigmented neurofibroma. Conclusions: Although PN is a rare subtype of neurofibroma, it is considered a chronically progressive benign tumor containing melanin-producing cells. These lesions can appear alone or in association with neurofibromatosis. Since this is a tumor that can be confused with other skin lesions, biopsy analysis is essential to differentiate it from other pigmented skin tumors, such as melanocytic schwannoma, dermatofibrosarcoma protuberans, neurocristic hamartoma, or neuronevus. Surveillance is part of the treatment, and surgical resection is sometimes performed.